Use of high pathogenicity avian influenza propagation models in the Dominican Republic - Gonzalez, Dejelia Ramona Gomez (2017)
The use of epidemiological models as a tool to evaluate the behavior of some diseases is increasingly common. Models have been used to represent infection with avian influenza, based on the history of outbreaks caused by the highly pathogenic H5N1 subtype, besides that, within-flock transmission due to H7N7 has been modeled from mortality data. The first outbreaks of influenza in poultry in the Americas arose from subtype H5N2; since then and for more than 30 years the subtype H5N2 North American lineage has been detected in other countries of the Americas. A virus of the same subtype and lineage was detected in 2007 in the Dominican Republic; to study the possible impact of an outbreak on the population we have developed a SIR model with several infection scenarios using parameters from the H5N2 North American lineage. The study was based on a real population through the poultry network contact of 951 farms; high and low pathogenic transmission was represented during a period of 100 days without the use of control strategies. Six scenarios for highly pathogenic and six scenarios for low pathogenic were simulated with seven repetitions each; all scenarios led to outbreaks with similar progression with epidemic curve declining from day 34; in low pathogenic the infection is maintained over time.